2018
DOI: 10.1177/1687814018770497
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of eccentric block in a fully mechanical vertical drilling tool under the effect of torsional vibration

Abstract: In present, the drilling industry have to face the reality of low oil and gas prices, fully mechanical vertical drilling tool is likely to become the best choice for vertical drilling in the future. Without electric measurement and control system, the mechanical vertical drilling tool has a mechanically stable platform with gravity sensitivity. The stable platform included an eccentric block which is not only sensitive to gravity but also severely affected by torsional vibration. In this article, we reveal the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…When the inclination angle exists, the gravity block will produce a restoring torque that always points to the low side of the wellbore. Li et al [9] proved that, as shown in Figure 2, when the included angle of the heavy block is π, the largest restoring torque T E produced is as shown in the following equation:…”
Section: Force Analysis and Mathematic Model Of The Mavdt'smentioning
confidence: 99%
See 2 more Smart Citations
“…When the inclination angle exists, the gravity block will produce a restoring torque that always points to the low side of the wellbore. Li et al [9] proved that, as shown in Figure 2, when the included angle of the heavy block is π, the largest restoring torque T E produced is as shown in the following equation:…”
Section: Force Analysis and Mathematic Model Of The Mavdt'smentioning
confidence: 99%
“…More important, the all-metal structural design can withstand higher temperatures and high temperature environments such as ultra-deep wells and vertical wells with abnormal geothermal gradients. So, it becomes the only way to achieve active correction during drilling in high temperature and ultra-deep wells [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the eccentric block is usually symmetrical, the center of gravity is located on the Y axis (as shown in Figure 5a). The Y coordinate value of the gravity center can be obtained by using Equation ( 5) [13].…”
Section: Tool Face Angle Modelmentioning
confidence: 99%
“…For the stable platform, Wang et al have used experimental methods to study the variation of friction performance between the upper and lower plate valves under different working conditions [12]. Li et al have derived the stable position model of the eccentric block and investigated the dynamic characteristics of it under the effect of torsional vibration by using multi-body dynamics simulation method [13]. For the actuator, Zhang have studied the output characteristics of the pushing force through experimental methods [14].…”
Section: Introductionmentioning
confidence: 99%